Effect of a Steaming Treatment on the Alpha-Glucosidase Inhibitory Components in the Brown Alga Sargassum fusiforme - Xinxin Liu; Yipeng Gu; Yihao Zhou; Ruiqi Zhang; Tomoyuki Koyama (Molecules)
The brown alga Sargassum fusiforme (SF) is historically consumed as a food material in Japan. A steaming process is often required for SF products on the market due to their moderate hardness and astringent taste. This investigation aimed to elucidate the effect of steaming on the anti-diabetic activity of SF and its related chemical components. Acetone extracts of SF were prepared after it were steamed for 0, 1, 2, or 4 h (SF-0h, SF-1h, SF-3h, and SF-4h, respectively). Alpha-glucosidase inhibitory profiles of each SF extract were made based on activity-guided separation. The active fractions were collected and NMR was applied for a further chemical composition analysis. Our results suggested that total polyphenol levels decreased drastically after steaming, which resulted in a drop in α-glucosidase inhibitory activity. The fatty acid, pheophytin a, and pyropheophytin a contents were elevated significantly after steaming, which contributed to the majority of the activity of steamed SF (SF-1h). However, prolonging the steaming time did not significantly affect the activity of SF further since the content of free fatty acids in steamed SF (SF-2h and SF-4h) almost did not change with a longer time of steaming. Moreover, palmitic acid, 8-octadecenoic acid, and tetradecanoic acid were identified as the top three important fatty acids for the inhibition of α-glucosidase by steamed SF. Further molecular docking results revealed that these fatty acids could interact with residues of α-glucosidase via hydrogen bonds, salt bridges, and hydrophobic interactions. In conclusion, steaming altered the α-glucosidase inhibitory properties of SF by changing the contents of polyphenols, fatty acids, and chlorophyll derivatives.